Association between assisted reproductive technology and autism spectrum disorders in Iran: a case-control study - Ensiyeh Jenabi; Mahdieh Seyedi; Ronak Hamzehei; Saeid Bashirian; Mohammad Rezaei; Katayoon Razjouyan; Salman Khazaei (The Korean Pediatric Society, 2020)
Background Autism spectrum disorder (ASD) is a neurodevelopmental disorder defined by impairments in social interaction and verbal and nonverbal communication. Purpose Determine the association between use of assisted reproduction technology (ART) and the risk of ASD among children. Methods This case-control study included 300 participants (100 cases, 200 controls). The control group included women with a child aged 2-10 years without ASD, while the cases were women with a child aged 2-10 years with ASD. We used a researcher-made questionnaire. Data were analyzed using Stata ver. 14 at the 0.05 significance level. Results In the univariate analysis, there was significant association between child sex, delivery mode, history of preterm delivery, history of using ART, and maternal age at child's birth and the risk of ASD. After the adjustment for other variables, this association was significant for male sex (2.66; 95% confidence interval [CI], 1.11-4.31; P=0.001) and history of using ART (4.03; 95% CI, 1.76-9.21; P=0.001). Therefore, after the adjustment for confounder variables, there was no significant association between ART and the risk of ASD among children (4.98; 95% CI, 0.91-27.30; P=0.065). Conclusion After the adjustment for other variables, risk factors for ASD were male sex and history preterm delivery. Thus, there was no significant association between ART and the risk of ASD among children.